"I couldn't even do normal chores": a qualitative study of the impacts of injury for Māori. Issue 17 (14th August 2021) - Lambert, Michelle; Wyeth, Emma H.; Brausch, Shawnee; Harwood, Matire L. N.; Anselm, Deborah; Wright-Tawha, Tracey; Metzger, Barbara; Ellison, Peter; Derrett, Sarah
Abstract: Aims: To investigate the rehabilitation experiences of Māori who were still reporting disability 24 months after an injury resulting in hospitalisation. Methods: Participants had been hospitalised for an Accident Compensation Corporation (New Zealand's no-fault injury compensation insurer) entitlement claim injury between 2007 and 2009, and were experiencing disability 24 months post-injury. In-depth kanohi ki te kanohi (face-to-face) qualitative interviews with 12 participants aged between 37 and 71 years at the time of interviews were conducted. Interpretive analyses of interview transcripts, focused on the impacts of injury was conducted with the aid of NVivo software. Results: The overarching theme identified during the analysis was "Impact" with four sub-themes of: Impact on daily life; Impact on relationships, Impact on employment; and, long-term or ongoing impacts. Conclusions: For Māori living with disability 24 months after hospitalisation for injury, adjusting to life after the injury and the rehabilitation process was challenging. Participants discussed frustration with feeling dependent on others, being bored and feeling unfulfilled after their injury, and that many aspects of their lives were impacted on and not always in the expected directions. Many reported longer lasting impacts even after rehabilitation was completed. Implications for rehabilitation programmes e.g., strengthening programmes by taking into account issues discussed by participants, recognising the long-term impacts on both those injured and their whānau (family), and further investigations required are also discussed. IMPLICATIONS FOR REHABILITATION: Disability after injury can have long term impacts for injured Māori and their relationships. Social impacts can be perceived as more debilitating than the physical impacts after injury. Experiences of employment changes and future prospects are often difficult to navigate for Māori returning to work after an injury.